Spontaneous pregnancies and determinant factors in infertility: A cross-sectional study - Nasrin Saadati; Roshan Nikbakht; Alireza Sattari; Fatemeh Sadat Amininezhad (International Journal of Reproductive BioMedicine, 2020)
Background: The phenomenon of infertility may be derived from different factors - either in males or females or both genders, including few unexplained factors. It is generally managed by medical and surgical treatments. Objective: To find a relation of occurrence of spontaneous pregnancy (SP) with effective factors in infertility. Materials and Methods: This cross-sectional study was conducted at two referral infertility centers (university and privacy center) in the southwest of Iran from March 2015 and March 2016 on 655 infertile couples, who were divided in two groups of with (n = 31) and without (n = 624) SP. The variables included female and male age, male smoking, male job, the place of living, the causes of infertility, the type and duration of infertility, and the subgroups of infertility causes. Results: Infertility may be caused due to both male- and female- related factors (47.5%). While female-related infertility was found in 31.5%, male-related infertility in 14.5%, and infertility due to unexplained factors in 6.6% of our patients. The rate of SP was 4.7%, which had a significant relation with the duration of infertility (p = 0.01), with women's age (p = 0.048), unexplained infertility (p = 0.001), and husband's job (p = 0.004). Conclusion: The occurrence of SP in infertile couples was related to age of the female partner, the duration of unexplained infertility, and the male partner's job.